STRATEGI KOMUNIKASI PERSUASIF - Putri, Sekar; Amelia, Amelia (KOMUNIKASIA: Journal of Islamic Communication and Broadcasting, 2022)
The Subuhan Pangkalpinang Bikers Community is a forum for youth or bikers who want to study Islam together and participate in the morning prayer in congregation to enliven the existing mosques by persuading others. This type of research is qualitative description, using data collection techniques, observation, interviews, and documentation. The results showed that the subuhan Pangkalpinang biker community used persuasive communication strategies, namely psychodynamics, socio-cultural and meaning construction. In the psychodynamic strategy, namely through an approach that touches the emotional aspect through Islamic traps, studies, other activities to strengthen friendship, after that the Subuhan biker community provides motivations, understandings in order to influence people's cognitive. As for the socio-cultural strategy, the management of the Subuhan Pangkalpinang biker community utilizes the environment and culture to persuade people to a better and positive direction. In the meaning construction strategy, Subuhan bikers use social media as a forum to convey information related to the activities that have been carried out.